2018
DOI: 10.1177/2058738418788749
|View full text |Cite
|
Sign up to set email alerts
|

IAPP/amylin deposition, which is correlated with expressions of ASC and IL-1β in β-cells of Langerhans’ islets, directly initiates NLRP3 inflammasome activation

Abstract: Recent findings revealed that type 2 diabetes mellitus (T2D) is a chronic inflammatory disease and an islet amyloid polypeptide (IAPP)/amylin, is deposited within pancreatic islets. IAPP/amylin has been reported to activate NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome in infiltrated macrophages. NLRP3, an intracellular pattern recognition receptor, has been shown to recognize pathogens and/or metabolites and complexes with the adopter protein apoptosis-associated speck-like protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
(48 reference statements)
2
18
0
2
Order By: Relevance
“…Our results suggest that the inhibitor function of LL‐37 is mediated by binding to 1) early prefibrillar IAPP species and their sequestration into soluble, non‐fibrillar hetero‐assemblies and 2) IAPP fibrils and their conversion into seeding‐incompetent assemblies. Together with findings by others, our results support the hypothesis that LL‐37 secreted by pancreatic β‐cells or infiltrated neutrophils under conditions of pancreatic inflammation binds IAPP and suppresses its amyloid self‐assembly and related β‐cell damage, thus slowing down T2D pathogenesis (Scheme ) . Studies on the potential physiological relevance of the LL‐37/IAPP interaction are now of high priority.…”
Section: Methodssupporting
confidence: 88%
“…Our results suggest that the inhibitor function of LL‐37 is mediated by binding to 1) early prefibrillar IAPP species and their sequestration into soluble, non‐fibrillar hetero‐assemblies and 2) IAPP fibrils and their conversion into seeding‐incompetent assemblies. Together with findings by others, our results support the hypothesis that LL‐37 secreted by pancreatic β‐cells or infiltrated neutrophils under conditions of pancreatic inflammation binds IAPP and suppresses its amyloid self‐assembly and related β‐cell damage, thus slowing down T2D pathogenesis (Scheme ) . Studies on the potential physiological relevance of the LL‐37/IAPP interaction are now of high priority.…”
Section: Methodssupporting
confidence: 88%
“…Besides, TLR engagement resulting in the activation of the transcription factor NF-kB, acts as a first priming signal of the inflammasome by the upregulation of NLRP3 [ 54 , 55 ]. Thus, considering that some studies have shown that cross-β fibrils derived from the amyloid β-peptide [ 56 ] and IAPP [ 57 , 58 ] can activate the NLRP3 inflammasome, the stimulation of TLR2/6 by M2e-NFs could also result on inflammasome priming, a hypothesis that will need to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Another oligomer of amyloid, amyloid β, can induce IL-1β via NLRP3 inflammasomes in a process involving the phagocytosis of amyloid β in glial cells in patients with Alzheimer’s disease (AD) and subsequent lysosomal damage and release of cathepsin B [108]. ROS are considered to be involved in the activation of NLRP3 inflammasomes, and it was suggested that direct interaction between amyloidogenic peptide and NLRP3 could initiate NLRP3 inflammasome formation in a cell-free system [109, 110]. Both IL-1α and IL-1β gene polymorphisms have been reported to be associated with central obesity and metabolic syndrome in a population with coronary heart disease in an epidemiologic study [111].…”
Section: Biological Functions Of Interleukin-1mentioning
confidence: 99%